Atomic cluster structures, phase stability and physicochemical properties of binary Mg-X (X= Ag, Al, Ba, Ca, Gd, Sn, Y and Zn) alloys from ab-initio calculations. (April 2018) - Du, Jinglian; Zhang, Ang; Guo, Zhipeng; Yang, Manhong; Li, Mei; Xiong, Shoumei
Abstract: Both structural and physicochemical properties of binary Mg-X (X = Ag, Al, Ba, Ca, Gd, Sn, Y, Zn) intermetallics were studied by performing ab-initio calculations. It was shown that except for Mg-Zn and Mg-Ba alloys, the mass density of the other Mg-X intermetallics changed linearly as the X-content. The local atomic structural features of Mg-X alloys could be well represented by the characteristic principal clusters, which denote the short-range-order structure of the Mg-X alloys. The coordination number ( CN ) of these atomic clusters changed in-between 8 and 16, and most were 12 and 14. The structural stability of Mg-Al, Mg-Ba, Mg-Ag, Mg-Ca, Mg-Sn, Mg-Y and Mg-Gd intermetallics increased as the solute content, while that of Mg-Zn intermetallics decreased as the Zn-content. For each Mg-X alloy system, MgAl2, MgAg3, Mg17 Ba2, Mg2 Zn11, MgGd and MgY intermetallics had larger elastic moduli and higher hardness than the others. Besides, MgAg3 and MgZn2 exhibited better plasticity among these Mg-X intermetallics, as reflected by the Poisson ratio and Pugh ratio. All of these Mg-X intermetallics were both thermodynamically and mechanically stable phases, and exhibited conductive metallic features based on the band structures and density of states. Highlights: Except for Mg-Zn and Mg-Ba alloys, the mass density of the other Mg-X intermetallics changed linearly as the X-content. The coordination number ( CN ) of the binary Mg-X atomic clusters changed in-between 8 and 16, and most were 12 and 14. Except for Mg-Zn intermetallics, the structural stability of the other Mg-X intermetallics increased as the solute content. For each Mg-X system, MgAl2, MgAg3, Mg1 7Ba2, Mg2 Zn11, MgGd and MgY had larger elastic moduli and hardness than the others. All of the Mg-X intermetallics were both thermodynamically and mechanically stable, and exhibited conductive features.